ANALYSIS OF THE PERFORMANCES OF FOUR TOTAL STATION INSTRUMENTS IN CONTROL EXTENSION - Abubakar, Takana; Japhet, N.; Mono, J. G. (FUDMA Journal of Sciences, 2024)
In the Surveying profession, advanced and modern instruments are improving the accuracy and precision of measurement and observation. However, accessing these instruments, such as Total Stations (TS), must be done with caution. This study is aimed at evaluating and analyzing the performance of TS instruments in a horizontal control extension. To conduct this study, a closed traverse was carried out to extend horizontal control points using Leica 1201+ series TS. The observations were carried out three time for five days. The result serves as the base for comparison with other four TS instruments. The TS instruments used include: Ruide RTS-820 Series, Nikon TS DTM-352/332, Sokkia CX – 105 series, and Topcon Total Station GTW-210 Series. The four TS were used to run a closed traverse on these same reference points. The observed data was processed using the least square adjustment procedure. The Standard Deviation (SD) and Root Mean Square (RMS) of the mean coordinate values for the four TS were computed. The result shows the highest SD as 0.0137508m and the highest RMSE as 0.012663m. This signals that all the mean coordinates obtained by the four TS were relatively close to reference TS data and also, that the residuals of the coordinates did not differ significantly. The two-way ANOVA test carried out however, signifies that at 0.01 level of significance the result of the four TS instruments dose not differ from the reference TS. It is therefore concluded that, all the four TS instruments has no significant difference in terms...
Keywords: Total Station; Reference Station; Performance; Accuracy; Precision